Cryopreservation of Multicellular Spheroids Derived From Newborn Piglet Adrenal Glands - Plaksina, Ekaterina M.; Sidorenko, Olga C.; Bozhok, Galina A. (Problems of Cryobiology and Cryomedicine, 2017)
Application of special in vitro culture techniques for the cells, derived from different animal and human organs, makes possible the obtaining of multicellular spheroids (MSs), being the natural 3-D environment for cells unlike the standard culture with the cells in monolayer. Previously we have shown that MSs formed in the newborn piglet adrenal cell culture are capable to produce the neuroblast-like cells, expressing the neuronal marker Î²-III-tubulin. In the present work we have assessed the regimens for MSs cryopreservation using 5, 7 and 10% dimethyl sulfoxide (DMSO) and 25% fetal bovine serum (FBS). Analysis of some characteristics of cryopreserved MSs (surface adhesion, capability to produce the neuroblast-like cells and monolayer formation by fibroblast-like cells) allowed to choose the cryopreservation regimen with 1Â°C/min cooling rate in the presence of 10% DMSO as the most optimal one. The FBS supplement to the medium did not significantly affect the cryopreservation outcome, although there was found a tendency to increase the capability of cryopreserved MSs to produce the neuroblast- and fibroblast-like cells. Probl Cryobiol Cryomed 2017; 27(4): 322-333